1998
DOI: 10.1597/1545-1569(1998)035<0040:ioclap>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cleft Lip and Palate and Risks of Additional Malformations

Abstract: Preterm cleft children with low birth weight should be screened for the presence of other birth defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 0 publications
6
51
2
1
Order By: Relevance
“…19 The types of clefts are distributed differently; the incidences vary in different population groups. 24,[27][28][29] Our findings showed that there were more CLP compared with isolated CP or CL; this result is similar to that of SouzaFreitas et al 30 On the other hand, Stoll et al 26 found higher rates of isolated CP compared with CLP. The extension and location were as follows: 3 patients (20%) with unilateral left complete CLP, 4 patients (26.7%) with unilateral right complete CLP, 4 patients (26.7%) with bilateral complete CLP, 3 patients (20.05%) with isolated CP, and 1 patient and 5 to 8% in first degree consanguineous marriages.…”
Section: Discussionsupporting
confidence: 83%
“…19 The types of clefts are distributed differently; the incidences vary in different population groups. 24,[27][28][29] Our findings showed that there were more CLP compared with isolated CP or CL; this result is similar to that of SouzaFreitas et al 30 On the other hand, Stoll et al 26 found higher rates of isolated CP compared with CLP. The extension and location were as follows: 3 patients (20%) with unilateral left complete CLP, 4 patients (26.7%) with unilateral right complete CLP, 4 patients (26.7%) with bilateral complete CLP, 3 patients (20.05%) with isolated CP, and 1 patient and 5 to 8% in first degree consanguineous marriages.…”
Section: Discussionsupporting
confidence: 83%
“…El tipo más común de hendidura en relación con alguna malformación fue el paladar hendido con el síndrome de Pierre Robín. 44 Bonaiti y colaboradores reporto también malformaciones adicionales en relación con las hendiduras palatinas aisladas entre las que se destacaron la secuencia de Pierre Robín, el síndrome de Ban der Woude, deficiencias mentales, enfermedades congénitas del corazón, polidactilia y sindactilia, entre otras. 45 Además, el LPH se ha asociado con polidactilia V, dislocación congénita, Síndrome de Stickeler, microftalmia, trisonomia 21, atresia gastrointestinal, Síndrome de Potter y translocacion autosomal, y Síndrome de Apert.…”
Section: Impacto Sobre La Condición Generalunclassified
“…Children with associated anomalies are more likely to have combined CLP or cleft palate, rather than cleft lip alone 8 . They are often of lower birth weight 10 . There are over 400 syndromes which include cleft lip and/or cleft palate as a component listed in the London Dysmorphology Database.…”
Section: Associated Anomaliesmentioning
confidence: 99%